A Miniaturized FBG Shape Sensor Based on a NiTi Substrate for Integration With Interventional Catheters - Sun, Lizhuang; Zhang, Weihan; Yang, Zhangrui; Tang, Yichao (Scientific Journal of Technology, 2026)
Three-dimensional catheter shape reconstruction is of considerable significance for minimally invasive cardiovascular navigation. This paper proposes a compact optical sensing scheme based on Fiber Bragg Gratings embedded in a NiTi-supported catheter structure. By combining strain-derived curvature estimation with Frenet-frame integration, the proposed method enables reconstruction of the catheter centerline from measured wavelength variations. The sensing structure is designed for improved compatibility with interventional catheter systems while maintaining a compact form factor. Static tests in planar and spatial bending configurations confirm that the reconstruction error remains within the millimeter range, demonstrating the practicality of the proposed approach.